Serum Ferritin Is Inversely Correlated with Testosterone in Boys and Young Male Adolescents: A Cross-Sectional Study in Taiwan - Chao, Kuo-Ching; Chang, Chun-Chao; Chiou, Hung-Yi; Chang, Jung-Su (PLOS ONE, 2015)
Objective The transition from childhood to teenaged years is associated with increased testosterone and a decreased iron status. It is not clear whether higher testosterone levels cause the decreased iron status, and to what extent, obesity-related inflammation influences the iron-testosterone relationship. The aim of the present study was to examine relationships of testosterone, iron status, and anti-/proinflammatory cytokines in relation to nutritional status in boys and young adolescent Taiwanese males. Methods In total, 137 boys aged 7 13 yr were included. Parameters for obesity, the iron status, testosterone, and inflammatory markers were evaluated. Results Overweight and obese (ow/obese) boys had higher mean serum testosterone, interleukin (IL)-1β, and nitric oxide (NO) levels compared to their normal-weight counterparts (all p<0.05). Mean serum ferritin was slightly higher in ow/obese boys compared to normal-weight boys, but this did not reach statistical significance. A multiple linear regression showed that serum ferritin (β = -0.7470, p = 0.003) was inversely correlated with testosterone, while serum IL-10 (β = 0.3475, p = 0.009) was positively associated with testosterone after adjusting for covariates. When normal-weight boys were separately assessed from ow/obesity boys, the association between testosterone and serum ferritin became stronger (β = -0.9628, p<0.0001), but the association between testosterone and IL-10 became non-significant (β = 0.1140, p = 0.4065) after adjusting for covariates. In ow/obese boys, only IL-10 was weakly associated with serum testosterone (β = 0.6444, p = 0.051) after adjusting for age. Conclusions Testosterone and serum ferritin are intrinsically interrelated but this relationship is weaker in ow/obese boys after adjusting for age.